Postoperative Recovery Patterns of Stented vs. Non-Stented Pyeloplasty in Pediatric Ureteropelvic Junction Obstruction (IAHS Medical Journal, 2025)
Background: Pediatric Ureteropelvic Junction (UPJ) obstruction is a common cause of hydronephrosis and can significantly affect renal function if left untreated. Pyeloplasty, both with and without stenting, is the gold-standard surgical treatment. This study aims to compare the postoperative recovery patterns between stented and nonstented pyeloplasty in pediatric UPJ obstruction.Materials and methods: This quasi-experimental study was conducted at the Department of Paediatric Surgery, Mymensingh Medical College Hospital, Mymensingh, from July 2021 to December 2021. A total of 31 children who underwent pyeloplasty were selected as study subjects by purposive sampling technique. A p-value less than or equal to 0.05 was considered as significant. Statistical Package for Social Sciences (SPSS) version 26.0 was used for this purpose.Results: The study revealed that anatomical parameters improved significantly in the stented group: APD decreased from 50.01 mm before surgery to 22.86 mm after 3 months (p=0.01) and cortical thickness increased from 3.02 mm to 4.28 mm (p=0.04). Serum Response Factor (SRF) showed minimal change in the stented group (p=0.584 before vs. 1.5 months, p=0.03 before vs. 3 months). In the non-stented group, APD improved from 47.06 mm to 22.80 mm (p=0.02), but cortical thickness showed no significant change (p=0.06). No significant difference in serum creatinine levels was observed between the groups.Conclusion: This study suggests that stented pyeloplasty results in a faster recovery in terms of anatomical parameters such as APD and cortical thickness. However, functional recovery, as assessed by SRF and serum creatinine levels, showed minimal difference between the stented and non-stented groups. This supports the idea that while stenting may facilitate more rapid anatomical improvement, the ultimate functional recovery of the kidney may not be significantly affected by the presence or absence of a stent.IAHS Medical Journal Vol 7(2), December 2024; 58-63